A Review of Probabilistic Approaches for Available Transfer Capability Calculation - Mohammed, O. O.; Mustafa, M. W.; Otuoze, A. O.; Salisu, S.; Abdulrahman, A. Y. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Several deterministic approaches have been proposed in literature for available transfer capability (ATC) computation. However, the gradual shift in power generation sources from fossil fuels to renewable energy sources has a remarkable influence on the ATC evaluation. The deterministic approaches do not incorporate the uncertainties of the renewable energy sources efficiently, therefore, various probabilistic techniques have been proposed in literature. This article presents a review of the various probabilistic methods for ATC computation. It provides the background, techniques and the features of ATC. Several contributions made by researchers, using probabilistic techniques for ATC computation, have been highlighted in this paper. This review has shown that there is a need for improvement in the existing approaches in order to evaluate ATC accurately. The improvement includes the development of a robust technique incorporating the system uncertainties and the uncertainties due to the renewable energy system as well as complete system dynamics in ATC computation. In addition, evaluation of ATC incorporating the transfer capability margins (TRM and CBM) is necessary to avoid over-/under-estimation of ATC value. This review will serve as a guide for the entrants in this research area.